Safety of Intravenous Push Lacosamide Compared With Intravenous Piggyback at a Tertiary Academic Medical Center. Issue 2 (February 2021) - McLaughlin, Kevin; Carabetta, Shannon; Hunt, Nicholas; Schuler, Brian R.; Ting, Clara; Tran, Lena K.; Szumita, Paul M.; Anger, Kevin E.
Background: There are limited data regarding the incidence of adverse events associated with administering lacosamide by intravenous push (IVP) compared with IV piggyback (IVPB). Objective: The objective of this analysis was to compare the safety profile, including cardiovascular effects, sedative effects, and IV site reactions of IVP and IVPB lacosamide administration. Methods: A retrospective pre/post cohort analysis comparing patients who received lacosamide via IVP and IVPB was conducted. Safety end points included hypotension, bradycardia, medication-related sedation, and IV site reactions. The relationship between patient characteristics and the incidence of safety end points was analyzed using the Student t -test and χ 2 test as appropriate. Results: Bradycardia occurred after 0.19% of IVP administrations and 1.09% of IVPB administrations assessed ( P = 0.07). Hypotension was observed in 3.16% of IVP administrations compared to 1.59% in the IVPB cohort ( P = 0.12). Post lacosamide-related sedation was noted in 11.32% and 11.68% of the IVP and IVPB cohorts, respectively ( P = 0.87). Infusion site reaction rates of 1.80% and 0.84% were documented in the IVP and IVPB cohorts, respectively ( P = 0.33). Of note, only 1 adverse event required clinical intervention. One 200-mg dose in the IVP cohort required a fluid bolus postadministration. Conclusion and Relevance: IVP lacosamide was associated with a similar incidence of cardiovascular, neurological, and infusion site–related adverse events compared with IVPB, in which nearly every adverse event was deemed clinically insignificant. Lacosamide administered via IVP may be considered a safe alternative method of administration in the acute care setting.